Astrocytes-associated research in Parkinson’s disease: an explored trends analysis - Yan-Jun Chen; Yan-Jun Chen; Ming-Rong Xie; Sheng-Qiang Zhou; Fang Liu (Frontiers in Aging Neuroscience)
BackgroundParkinson’s disease (PD) is characterized pathologically by the degeneration of dopaminergic neurons and the formation of Lewy bodies. Among the various cellular and molecular mechanisms of PD, astrocyte dysfunction is one of the causes of disease development. This study aims to explore the research hotspots, frontiers, and prospective directions regarding PD and astrocytes.MethodRelevant academic publications were searched through the Web of Science database. CiteSpace, VOSviewer, and bibliometrix were used for visualization and quantitative evaluation.ResultsA total of 2,408 publications related to the study topic were included in the analysis. From 2001 to 2024, annual publications gradually increased. Activated countries were concentrated in North America, Asia, and Europe. The United States and China were the main research leaders. Nanjing Medical University was the active institution with the largest number of publications, and the University of Cambridge had the highest influence on publications. International Journal of Molecular Sciences was the core journal with the most publications. Dr. Hu, Gang was the most productive author, and Dr. Saarma, Mart was the most influential author. Research hotspots included astrocytes, PD, neuroinflammation, alpha-synuclein (α-Syn), microglia, oxidative stress, and neurodegeneration. In recent years, NLRP3 inflammasome, extracellular vesicles (EVs), and signaling pathway were the research topics with strong burst power.ConclusionCollaboration among different countries, organizations, and authors has effectively promoted the rapid development of this field, and the research achievements have gradually increased. The research hotspots mainly focused on neuroinflammation, α-Syn, microglia, oxidative stress, and neurodegeneration. NLRP3 inflammasome, EVs, and signaling pathway are research directions in the future.